Polyamide powder particles and their use in powder agglomeration processes
Patent Information
- Application Number
- JP2021561961
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-04-19
- Filing Date
- 2020-04-16
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2040-04-16
Smart Images

Figure 0007644024000002 
Figure 0007644024000001
Abstract
Description
[Technical Field]
[0001] The present invention relates to polyamide powder seed particles and their use in a powder agglomeration process for producing three-dimensional objects that are easy to clean by layer-by-layer fusing. [Background technology]
[0002] The technique for agglomerating polyamide powders is used to manufacture three-dimensional objects such as prototypes and models, especially in the automotive, marine, aviation, aerospace, medical (prosthetics, hearing systems, etc.), textile, clothing, fashion, decoration, electronic housing, telecommunications, home automation, computing and lighting sectors. This technique also makes it possible to achieve fine and complex shapes that are not possible with conventional molding techniques.
[0003] The agglomeration of the powder by melting (hereinafter "sintering") is brought about by radiation, such as, for example, a laser beam (laser sintering), infrared radiation, UV radiation, or any source of electromagnetic radiation that makes it possible to fuse powder layers layer by layer to produce a three-dimensional object.
[0004] In laser sintering, a thin layer of polyamide powder is deposited on a horizontal plate maintained in a chamber heated to a temperature between the polyamide powder's crystallization temperature Tc and melting temperature Tm. The laser allows the powder particles at various points in the slowly crystallizing layer to fuse into the corresponding geometric shape of the object after the laser's passage, for example, using a computer that memorizes the shape of the 3D object in a memory device and reproduces this shape in the form of a 2D thin piece. The horizontal plate is then lowered by a value corresponding to the thickness of the powder layer (for example, between 0.05 and 2 mm, typically around 0.1 mm), and a new powder layer is then deposited. The laser allows the powder particles to fuse together, etc., according to the geometric shape of this new slowly crystallizing layer. This procedure is repeated until the entire object is produced. The object is obtained, surrounded by powder in the chamber. The unagglomerated portions therefore remain in powder form. After complete cooling, the object is separated from the powder, which can be reused for another operation.
[0005] If the temperature of the powder in the machine is too close to the powder's melting temperature (Tm), solidification around the part (the "caking" phenomenon) occurs, which manifests as undesirable agglomerations of powder in certain places on the object's surface instead of a good definition of the final object. Therefore, at the end of a build, also called a "run," the parts must be cleaned before they can be used again in order to remove any powder that may have remained attached to the parts. This cleaning is typically done by sandblasting, which can lead to the degradation of certain fine and / or fragile elements of the built 3D part.
[0006] Currently, there are no known techniques to solve this problem other than cleaning the parts. Today, for all users of 3D printing equipment, the ease and time required to clean parts are two critical factors in overall manufacturing costs. In the specific case of polyamide powder, certain grades are particularly time-consuming to clean. Furthermore, certain geometries are not accessible for cleaning, even though the production of parts with complex and fine features is precisely the benefit offered by 3D printing. Summary of the Invention
[0007] The inventors have unexpectedly demonstrated that seed particles of core / shell polyamide powders formed from a polyamide shell with high molar mass and high melting temperature around a polyamide core facilitate and / or reduce the time required for cleaning objects obtained from these powders by additive manufacturing (known under the term 3D printing). Advantageously, the inventors have also demonstrated that these polyamide powders are easily recyclable.
[0008] The subject of the present invention is therefore - a polyamide core with a volume median diameter D50 in the range of 15 to 60 μm, and - Polyamide shell The shell is characterized by having an intrinsic viscosity in solution and a melting temperature that are equal to or higher than those of the core.
[0009] The present invention also relates to a method for producing polyamide powder particles as defined above, by anionic polymerization in solution in a solvent, comprising the polymerization of a shell from 2-pyrrolidone (lactam 4), caprolactam (lactam 6), 2-azacyclononanone (lactam 8), lauryllactam (lactam 12) or mixtures thereof in the presence of a catalyst, an activator and at least one amide selected from N,N'-alkylenebisamides around seeds selected from the group consisting of PA4, PA6, PA8, PA11, PA12, PA6 / 12, PA6.12, PA6.13, PA6.10, PA6.6 and PA10.10, which form the core of the particle.
[0010] The invention also relates to a method for producing powder particles according to the invention by dissolving the shell polyamide in an alcohol-based solvent followed by precipitation of the shell polyamide around the core of the particle.
[0011] The present invention also relates to the use of the polyamide powder as defined above in a composite material, a substrate coating, a transfer paper or for producing a cosmetic composition.
[0012] The present invention also relates to the use of a polyamide powder as defined above for producing an object, by agglomerating said powder by melting brought about by radiation selected from laser light, infrared radiation or UV radiation.
[0013] The present invention also relates to the use of the polyamide powder defined above in an additive manufacturing process to reduce the phenomenon of agglomeration of the powder on the surface of an object.
[0014] The present invention also relates to a method for producing an object by agglomeration of the polyamide powder defined above, during which: a. depositing a thin layer of powder (Layer 1) onto a horizontal plate maintained in a chamber heated to a temperature between the crystallization temperature (Tc) and melting temperature (Tm) of the powder; b. The input of laser or electromagnetic energy causes the particles to agglomerate by melting at various points in the powder layer (layer 1) according to the geometric shape corresponding to the object to be manufactured; c. The horizontal plate is then lowered by a value corresponding to the thickness of one powder layer, and then a new powder layer (layer 2) is deposited; d. The input of laser or electromagnetic energy causes the particles to coalesce by melting the powder layer (layer 2) according to the geometric shape corresponding to this new slice of the object to be produced; e. Repeat the previous steps until the object is constructed. f. A powder-rimmed object is obtained in the chamber; g. After complete cooling, the object is separated from the powder, which can be reused for another operation. DETAILED DESCRIPTION OF THE INVENTION
[0015] definition In the sense of the present invention, the term "3D printing" or "additive manufacturing" is understood to mean any method for the mass production of parts by layer-by-layer powder addition or agglomeration. In the sense of the present invention, the term "3D printing" or "additive manufacturing" is understood to mean selective sintering techniques using absorbents, in particular the techniques known under the names "high speed sintering" (HSS) and "multi-jet fusion" (MJF).
[0016] In this specification, the term "sintering" includes all these methods, regardless of the type of radiation. In the following text, even if reference is generally made to the selective laser sintering method, what is written about this method is of course also valid for other manufacturing methods.
[0017] In the description of the invention, including the examples that follow, the D50 of a powder, also called "volume median diameter", corresponds to the particle size value that divides the examined population exactly by 2. D50 can be measured according to standard ISO 9276 Parts 1-6: "Representation of results of particle size analysis", or according to standard ISO 13319. Preferably, standard ISO 13319:2007 is followed. In this description, a Multisizer 3 Coulter Counter particle sizer from Beckman Coulter is used to determine the particle size distribution of the powder, from which D50 is estimated.
[0018] The intrinsic viscosity in solution (especially of polyamides, powder or sintered parts) is measured in accordance with standard ISO 307:2007 at a concentration of 0.5% by weight in m-cresol solution relative to the total weight of the solution, at a temperature of 20°C, using an Ubbelohde viscometer.
[0019] The analysis of the thermal properties of polyamides is carried out by DSC according to standard ISO 11357-3 "Plastics - Differential Scanning Calorimetry (DSC) Part 3: Determination of temperature and enthalpy of melting and crystallization." The temperatures more specifically relevant to the present invention are the first heat melting temperature and melting enthalpy (Tm1, ΔHf1), and the crystallization temperature (Tc). Preferably, a high melting enthalpy allows for better geometric definition of the parts produced by the additive manufacturing process.
[0020] The term "caking" is understood to mean the phenomenon of powder agglomeration, which manifests itself in the presence of undesirable powder agglomerates at certain locations on the surface of the object, instead of having good definition of the final object. This phenomenon is observed when the conversion temperature in the equipment is too close to the melting temperature (Tm) of the powder.
[0021] Polyamide powder particles The subject of the present invention is a seed polyamide (PA) powder consisting of a shell made of polyamide and a core made of polyamide, the core and the shell being either of the same type of polyamide but differing in weight-average molar mass (Mw) or of different types of polyamide.
[0022] According to one embodiment, the polyamide (PA) is an aliphatic polyamide or an aliphatic copolyamide.
[0023] Preferably, the shell and the core are made of a polyamide selected from the group consisting of PA4, PA6, PA8, PA11, PA12, PA6 / 12, PA6.12, PA6.13, PA6.10, PA6.6 and PA10.10.
[0024] Preferably, the shell and core of the particles according to the invention are as follows: - shell and core made of PA6, or - shell and core made of PA12, or - Shell and core made of PA6 / 12.
[0025] Likewise, preferably the shell and the core are different types of polyamide. Preferably, the shell and the core of the particles according to the invention are as follows: - a shell made of PA6 and a core chosen from PA8, PA11, PA12, PA6 / 12, PA6.12, PA6.10, PA10.10, or - a shell made of PA12 and a core chosen from PA6 / 12, PA6.12, or - Shell made from PA6 / 12 and core chosen from PA11, PA12, PA6.12, PA10.10, PA6.10.
[0026] Preferably, the core has a volume median diameter (x) between 15 and 60 μm. According to embodiments, the core has a volume median diameter (x) between 15 and 20 μm, or between 20 and 25 μm, or between 25 and 30 μm, or between 30 and 35 μm, or between 35 and 40 μm, or between 40 and 45 μm, or between 45 and 50 μm, or between 50 and 55 μm, or between 55 and 60 μm.
[0027] Preferably, the shell has a thickness (y) between 1 and 15 μm.
[0028] Preferably, the powder particles according to the invention have a volume median diameter (x+2*y) between 17 and 90 μm, more preferably between 35 and 55 μm.
[0029] Preferably, the shell has a melting temperature above 180°C, preferably in the range of 183°C to 185°C.
[0030] Preferably, the shell has an intrinsic viscosity between 1.20 and 1.50, preferably between 1.35 and 1.45.
[0031] Preferably the core has a melting temperature above 140°C, preferably between 175°C and 180°C.
[0032] Preferably, the core has an intrinsic viscosity between 0.30 and 1.30, preferably between 0.75 and 1.05.
[0033] Preferably, the powder particles according to the invention have a melting temperature above 180°C.
[0034] Preferably, the powder particles according to the invention have an intrinsic viscosity between 1.20 and 1.35.
[0035] Advantageously, the polyamide powder according to the invention facilitates the cleaning of objects shaped by an additive manufacturing process and shortens the time therefor. Similarly advantageously, the polyamide powder according to the invention reduces the risk of breakage when cleaning objects having a very fine geometry.
[0036] Method for producing polyamide powder particles In one embodiment of the invention, the powder particles according to the invention are prepared by dissolving a shell polyamide in an alcohol-based solvent and then precipitating the shell polyamide around the core of the particles. The dissolution is preferably carried out under pressure and / or under heating. Similarly preferably, the dissolution is carried out in the presence of the core of the particles in a suspension in the solvent. Preferably, the precipitation is carried out by a decrease in temperature and / or by extraction of the solvent.
[0037] The subject of the invention is also a method for producing a powder by anionic polymerization in a solution in a solvent.
[0038] <A. Components of polymerization> - Monomer Preferably, the polymerization is carried out in a solution of the lactam or mixture in a solvent in the presence of at least one amide selected from a seed (or organic filler) which is a particle of a powder of PA4, PA6, PA8, PA11, PA12, PA6 / 12, PA6.12, PA6.13, PA6.10, PA6.6 and PA10.10, a catalyst, an activator and N,N'-alkylenebisamide, in the presence of lauryllactam (lactam 12), caprolactam (lactam 6), 2-pyrrolidone (lactam 4), or 2-azacyclononane (lactam 8) monomer, or a mixture thereof.
[0039] - Solvent The solvent used dissolves the monomer but does not dissolve the polymer particles formed during the polymerization. Advantageously, the solvent is a paraffinic hydrocarbon fraction having a boiling range between 120 and 170°C, preferably between 140 and 17°C.
[0040] The solvent can be supersaturated with the monomer at the polymerization temperature. The solvent can be supersaturated with the monomer by various means. One of these means can consist of saturating the solvent with the monomer at a temperature above the initiation temperature and then lowering the temperature to the initiation temperature. Another means can consist of substantially saturating the solvent with the monomer at the initiation temperature and then, still at this temperature, adding a primary amide, preferably containing 12 to 22 carbon atoms, such as oleamide, N-stearamide, erucamide, isostearamide, or N,N'-alkylenebisamide (examples of which are given below).
[0041] It is also possible to carry out the polymerization in a solvent that is not saturated with monomer, in which case the reaction medium contains the monomer dissolved in the solvent at a concentration far from supersaturation at the initiation temperature.
[0042] - Catalyst Preferably, a catalyst selected from the usual catalysts for the anionic polymerization of lactams is used. This is a base strong enough to produce lactamate after reacting with the lactam. A combination of several catalysts is possible. Non-limiting examples include sodium hydride, potassium hydride, sodium, sodium methoxide and / or sodium ethoxide. The amount of catalyst introduced generally varies between 0.5 and 3 mol per 100 mol of monomer.
[0043] - Activator It is also preferred to add an activator, which serves to bring about and / or accelerate the polymerization. The activator is selected from lactam-N-carboxyanilide, (mono)isocyanate, polyisocyanate, carbodiimide, cyanamide, acyllactam and acylcarbamate, triazine, urea, N-substituted imide, ester, and phosphorus trichloride. Optionally, the activator may also be a mixture of several activators. The activator can also be formed in situ, for example, by the reaction of an alkyl isocyanate with a lactam to give an acyllactam.
[0044] Preferably, the catalyst / activator molar ratio is between 0.2 and 2, preferably between 0.8 and 1.2.
[0045] - Amide Preferably, at least one amide is also added, one of which is always an N,N'-alkylenebisamide. The amount of N,N'-alkylenebisamide introduced is generally about 0.001 to 4 mol, preferably about 0.075 to 2 mol, per 100 mol of monomer. Among the N,N'-alkylenebisamides that are particularly recommended are N,N'-alkylenebisamides of fatty acids, and even more preferably, the following: - Formula C 17 H 35 -C(=O)-NH-CH2CH2-NH-C(=O)-C 17 H 35 N,N'-ethylenebisstearamide (abbreviated as EBS), and - Formula C 17 H 33 -C(=O)-NH-CH2CH2-NH-C(=O)-C 17 H 33 N,N'-ethylenebisoleamide (abbreviated as EBO), N,N'-Alkylenebispalmitamides, N,N'-Alkylenebisgadoleamides, N,N'-Alkylenebiscetreamides, and N,N'-Alkylenebiserucamides.
[0046] The use of EBS and / or EBO is preferred.
[0047] It is also possible to add primary amides, preferably containing 12 to 22 carbon atoms, which are preferably chosen from oleamide, N-stearamide, isostearamide, erucamide.
[0048] - Organic fillers Regarding the organic filler, this preferably relates to homopolyamide or copolyamide powder, preferably PA4, PA6, PA8, PA11, PA12, PA6 / 12, PA6.12, PA6.13, PA6.10, PA6.6 and PA10.10. Examples include Orgasol(R) powder manufactured by Arkema, Rilsan(R) fine powder manufactured by Arkema, Vestosint(R) powder manufactured by Evonik, MICROPAN(R) powder manufactured by Chemopharma, etc.
[0049] The polyamide powder is preferably finely divided.
[0050] The amount of the organic filler and the diameter of the filler make it possible to induce the size of the final particles obtained at the end of polymerization in the desired direction (small particles or large particles).
[0051] - Other fillers or additives Also, it is possible to add any type of filler (dyes, pigments, carbon black, carbon nanotubes, etc.) or additives (antioxidants, anti-UV agents, plasticizers, etc.) well-known to those skilled in the art to the reaction medium. However, this is subject to the condition that all of these compounds are completely dry and inert with respect to the reaction medium.
[0052] <B. Polymerization> Anionic lactam ring-opening polymerization is carried out continuously or preferably batchwise. After introducing the solvent batchwise, the monomer, optionally N,N'-alkylenebisamide, filler, catalyst and activator are introduced simultaneously or continuously. First, the solvent and monomer are introduced, and then, for example, after removing all trace amounts of water using azeotropic distillation, it is recommended to add the catalyst once the medium becomes anhydrous. The filler can be introduced, for example, after the introduction of the monomer. To avoid loss of coagulation or polymerization control, it may be advantageous to introduce the activator gradually or at a certain introduction rate rather than all at once.
[0053] The polymerization is carried out at atmospheric pressure or slightly higher (partial pressure of the hot solvent) and at temperatures between 20°C and the boiling point of the solvent. The initiation and polymerization temperatures of the lactam are generally between 70 and 150°C, preferably between 80 and 130°C. Advantageously, the polymerization temperature of the lactam is below 120°C and above 70°C.
[0054] The weight ratio, expressed in %, of organic filler / monomer introduced into the reaction medium is between 0.001% and 65%, preferably between 0.005% and 45%, even more preferentially between 0.01% and 30% and advantageously between 0.05% and 20%.
[0055] The seed powder obtained at the end of the polymerization is preferably insoluble in the solvent of the monomers previously introduced into the reaction medium.
[0056] Use of polyamide powder particles Preferably, the polyamide powder according to the invention is used in a method for producing an object by agglomeration of the powder by a radiation-assisted melting or sintering method. The radiation can be selected from any radiation known to those skilled in the art. Examples of radiation include a laser beam (laser sintering), infrared radiation, UV radiation, or any electromagnetic radiation source that allows the layer-by-layer melting of powder layers to produce a three-dimensional object.
[0057] The equipment used can be any sintering equipment known to those skilled in the art, including, by way of example, sintering equipment sold by EOS, 3D Systems, Aspect, Trump Precision Machinery, Hewlett Packard, Sinterit, Sintratec, Sharebot, FormLabs, Sonda Sys, Farsoon, Prodways, Ricoh, Wematter3D, VoxelJet, Xaar, etc. Examples of sintering equipment include EOSINT P396 and Formiga P100 manufactured by EOS GmbH.
[0058] The objects produced by agglomeration of the powders according to the invention are preferably 3D objects, preferably selected from the fields of prototypes, part models ("rapid prototyping"), small series of finished parts ("rapid manufacturing") for automotive, marine, aviation, aerospace, medicine (prosthetics, hearing systems, etc.), textiles, clothing, fashion and decoration, housings for electronic devices, telecommunications, home automation, computing, lighting, sports and tools.
[0059] Advantageously, the use of the polyamide powder according to the invention in a 3D printing process makes it possible to reduce the phenomenon of agglomeration of the powder on the surface of the 3D object. The use of the powder according to the invention in additive manufacturing is particularly advantageous, since it makes it possible to facilitate and / or shorten the cleaning time of the objects obtained by this technique.
[0060] The use of the powder according to the invention in additive manufacturing is particularly advantageous since it can be recycled multiple times, either alone or in a mixture. Specifically, the unconverted powder can be recovered by screening, the screen thus retaining the 3D part and allowing the powder to pass through. Preferably, the powder according to the invention can be recycled at least three times, preferably at least five times, more preferably at least ten times.
[0061] Preferably, in each build cycle, or "run," the recycled powder content is at least 50 wt.%, preferably at least 60 wt.%, and more preferably at least 70 wt.%, based on the total weight of powder used in the machine in each run. In other words, except for the first run, which uses 100% fresh powder, each subsequent run reuses at least 50 wt.%, preferably at least 60 wt.%, and preferably at least 70 wt.%, of the powder from the previous run that was not sintered, based on the total weight of powder used in the machine in each run.
[0062] Prior to use, the object can be easily cleaned using any cleaning technique known to those skilled in the art, for example, the object can be cleaned using a sandblaster.
[0063] Non-limiting examples of the present invention are given below. [Brief explanation of the drawings]
[0064] [Figure 1] Shown are four parts built by the selective laser sintering (SLS) method, each with 10 holes of different sizes. The cleaning characteristics of the parts were investigated using a compressed air blower without sandblasting. A score of 10 is given depending on the number of unclosed holes. The first part from the top has a score of 0 / 10. The second part from the top has a score of 6 / 10. The third part from the top has a score of 8 / 10. The fourth part from the top has a score of 10 / 10. [Example]
[0065] The inventors investigated the phenomenon of powder agglomeration (caking), which manifests as the presence of powder agglomerations at specific locations on the surface of a 3D object produced by an additive manufacturing process.
[0066] <1. Preparation of polyamide powder according to the present invention> 1.1. Preparation of PA12 Seed PA12 Powder A reactor maintained under nitrogen is charged with 2800 ml of solvent, followed by 716 g of lactam 12, 8.2 g of EBS, and 203 g of Orgasol® 2002 ES3 Nat3 (PA12 powder). After starting stirring at 350 rpm, the mixture is gradually heated to 110°C, followed by distillation of 360 ml of solvent under vacuum, azeotropically entraining any traces of water that may be present.
[0067] After returning to atmospheric pressure, the anionic catalyst, 2.9 g of sodium hydride (60% purity in oil), is rapidly introduced under nitrogen, stirring is increased to 400 rpm and stirring is continued at 105° C. under nitrogen for 30 minutes.
[0068] A small metering pump is used to continuously inject the selected activator, namely stearyl isocyanate (12.2 g made up to 189.6 g with solvent), into the reaction medium according to the following program: - 11 g / h of isocyanate solution for 180 min, - 45g / h isocyanate solution for 210 minutes.
[0069] At the same time, the temperature is maintained at 105° C. for 360 minutes during the injection, then raised to 130° C. in 30 minutes and maintained at this temperature for 3 hours after the introduction of the isocyanate has ended.
[0070] At the end of the polymerization, the polyamide powder is dispersed in the synthesis solvent. The reaction medium is cooled to 80°C so that the reactor can be emptied. After solid-liquid separation, the polyamide powder is placed in an oven at 75°C to dry the solvent.
[0071] <1.2. Powder properties> 1.2.1 Measurement method D50 is measured according to ISO standard 13319.
[0072] The intrinsic viscosity is measured according to ISO standard 307:2007 at a temperature of 20° C. and at a concentration of 0.5% by weight in meta-cresol solution relative to the total weight of the solution.
[0073] The melting temperature and enthalpy of fusion are measured by DSC according to ISO standard 11357-3 "Plastics - Differential Scanning Calorimetry (DSC) Part 3: Determination of temperature and enthalpy of melting and crystallization".
[0074] 1.2.2.Results The resulting core / shell polyamide powder particles have a volume median diameter of 43.1 μm, an intrinsic viscosity of 1.27, a melting temperature of 184° C. and a melting enthalpy of 115 J / g.
[0075] The core has a volume median diameter D50 of 30 μm, an intrinsic viscosity of 1.02 and a melting temperature of 177°C.
[0076] The shell was 6.5 μm thick, and synthesis parameters were chosen aiming for an intrinsic viscosity of 1.40 and a melting temperature of 184°C.
[0077] [2. Comparative Example] [2.1. Comparative Example 1: PA12 powder (PA2200, product sold by EOS)] The PA2200 powder particles have a volume median diameter of 52.7 μm, an intrinsic viscosity of 1.00, a melting temperature of 186° C., and a melting enthalpy of 125 J / g.
[0078] [2.2. Comparative Example 2: Silica Seed PA12 Powder] The PA12 powder particles described in Example 2 of patent FR2867190 have a volume median diameter of 51 μm without agglomerates, an intrinsic viscosity of 1.12, a melting temperature of 184° C. and a melting enthalpy of 118 J / g.
[0079] 3. Evaluation of powder agglomeration Procedure To evaluate the phenomenon of powder agglomeration due to melting, parts with 10 holes of different sizes that are particularly sensitive to caking were fabricated by the selective laser sintering (SLS) method using powder particles according to the present invention and powder particles according to Comparative Examples 1 and 2.
[0080] The cleaning characteristics of the parts were investigated using a compressed air blower without sandblasting. The greater the number of unclosed holes in a part, the easier it is to clean. A score of 10 was given according to the number of unclosed holes. Figure 1 shows an example of a part with 10 holes of different sizes and the scores that can be given according to the number of unclosed holes. A score of 10 / 10 is given to the easiest powder to clean, while a score of 0 / 10 is given to the powder that is strongly agglomerated and most difficult to clean (which may result in longer cleaning times and possibly degradation of certain fine and / or fragile elements of the printed 3D part).
[0081] 3.2.Conversion Conditions The laser conditions used in this test are those recommended for PA12 powder (PA2200).
[0082] [Table 1]
[0083] 3.3.Results Under the same operating conditions on a laser sintering (LS) machine - the powder according to the invention received a score of 8 / 10, since 8 out of 10 holes were not closed; - PA2200 powder (Comparative Example 1) received a score of 7 / 10 due to 7 out of 10 holes not closing; - Silica seeded PA12 powder (Comparative Example 2) received a score of 0 / 10 due to the closure of holes in the parts during cleaning.
[0084] As a result, the powder according to the invention is less prone to the formation of undesirable powder agglomerates than conventional polyamide powders. This is coupled with the fact that the powder according to the invention forms fewer powder agglomerates on the surface of the produced object. The object therefore has better final definition and is easier to clean than objects produced from conventional powders.
Claims
1. 1. Seed particles of polyamide (PA) powder, a polyamide core having a volume median diameter D50 in the range from 15 to 60 μm, and - Polyamide shell It consists of: The shell has an intrinsic viscosity in solution and a melting temperature higher than the intrinsic viscosity and melting temperature of the core, Seed particles.
2. 2. The particle according to claim 1, wherein the shell and the core of the particle are made of a polyamide selected from the group consisting of PA4, PA6, PA8, PA11, PA12, PA6 / 12, PA6.12, PA6.13, PA6.10, PA6.6 and PA10.
10.
3. 3. A particle according to claim 1 or 2, wherein the shell and the core of the particle are of the same nature: - shell and core made of PA6, or - shell and core made of PA12, or - shell and core made of PA6 / 12.
4. 3. The particle according to claim 1 or 2, wherein the shell and the core of the particle have different properties: a shell made of PA6 and a core chosen from PA8, PA11, PA12, PA6 / 12, PA6.12, PA6.10, PA10.10, or a shell made of PA12 and a core chosen from PA6 / 12, PA6.12, or a shell made of PA6 / 12 and a core chosen from PA11, PA12, PA6.12, PA10.10, PA6.
10.
5. A particle according to any one of claims 1 to 4, wherein the shell has an intrinsic viscosity in solution in the range of 1.20 to 1.
50.
6. 6. Particle according to any one of claims 1 to 5, wherein the shell has a melting temperature (Tm1) above 180°C.
7. Particles according to any one of claims 1 to 6, characterized in that the shell is obtained by anionic polymerization.
8. Particles according to any one of claims 1 to 6, characterized in that the shell is obtained by dissolution and precipitation of a polyamide around the core of the particle.
9. Particles according to any one of claims 1 to 8, characterized in that they have a volume median diameter D50 lying in the range of 17 to 90 μm.
10. A method for producing powder particles according to any one of claims 1 to 7 by anionic polymerization in solution in a solvent, comprising polymerizing a shell from 2-pyrrolidone, caprolactam, lauryllactam, 2-azacyclononanone, or mixtures thereof, in the presence of a catalyst, an activator, at least one amide selected from N,N'-alkylenebisamides, and an organic filler for the core of the particle selected from the group consisting of PA4, PA6, PA8, PA11, PA12, PA6 / 12, PA6.12, PA6.13, PA6.10, PA6.6 and PA10.
10.
11. The method according to claim 10, characterized in that the N,N'-alkylenebisamide is selected from EBS and EBO.
12. 12. The method according to claim 10 or 11, characterized in that in addition to the N,N'-alkylenebisamide, a further amide is present selected from oleamide, N-stearamide, isostearamide and erucamide.
13. 10. A method for producing powder particles according to any one of claims 1 to 6, 8 and 9, by dissolving the shell polyamide in an alcohol based solvent followed by precipitation of the shell polyamide around the core of the particle.
14. The method according to claim 13, wherein the dissolving is carried out under pressure and / or by heating.
15. 15. The method of claim 13 or 14, wherein the dissolution is carried out in suspension in the solvent in the presence of the cores of the particles.
16. The method according to any one of claims 13 to 15, wherein the precipitation is carried out by reducing the temperature and / or by extracting a solvent.
17. Use of the powder according to any one of claims 1 to 9 in a composite, a substrate paint, a transfer paper or for the manufacture of a cosmetic composition.
18. Use of a powder according to any one of claims 1 to 9 for producing an object by agglomerating said powder by melting brought about by radiation selected from a laser beam, infrared radiation or UV radiation.
19. Use of the powder according to any one of claims 1 to 9 in a 3D printing process to reduce the phenomenon of agglomeration of the cohesive powder on the surface of the 3D object.
20. A method for producing an object by agglomeration of a polyamide powder according to any one of claims 1 to 9, during which a. depositing a thin layer of powder (Layer 1) onto a horizontal plate maintained in a chamber heated to a temperature between the crystallization temperature (Tc) and the melting temperature (Tm) of the powder; b. The input of laser or electromagnetic energy causes the agglomeration of said particles by melting at various points of said powder layer (layer 1) according to the geometric shape corresponding to the object to be manufactured; c. Lower the horizontal plate by a value corresponding to the thickness of one powder layer and then deposit a new powder layer (layer 2); d. The input of the laser or electromagnetic energy causes the particles to coalesce by melting the powder layer (layer 2) according to a geometric shape corresponding to this new slice of the object to be produced; e. Repeating the previous steps until the object is constructed; f. obtaining a powder-rimmed object within said chamber; g. After complete cooling, the object is separated from the powder, which can be reused for another operation. method.
Citation Information
Patent Citations
Method for manufacturing polyamide 12 powder of high melting point
JP2005248180A
Core-shell polyamide powder
JP2010514877A
Powder comprising polymer-coated polymeric core particles
US9382420B2
Method for manufacturing three-dimensionally shaped object and three-dimensionally shaping device
WO2018087999A1
Powder material and method for producing three-dimensional model
WO2019013069A1